1997
DOI: 10.1074/jbc.272.10.6706
|View full text |Cite
|
Sign up to set email alerts
|

Preproparathyroid Hormone-related Protein, a Secreted Peptide, Is a Substrate for the Ubiquitin Proteolytic System

Abstract: , and Thr (T)) motif in the COOH-terminal region of the protein were not required as cis-acting determinants for ubiquitination. This is the first report of a wild-type secretory polypeptide serving as a substrate of the ubiquitin proteolytic pathway. These results suggest that the ubiquitin-dependent proteolytic pathway is involved in regulating the metabolic stability of intracellular PTHrP, and this regulation may be an important mechanism for modulating its effects on cell growth and differentiation.Parath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…The amino acid sequence of pro-PTHrP, a precursor of PTHrP, can serve as a substrate for the prohormone convertase furine (29). The PTHrP , detected in H295R cells, but not in adrenal tumors, is probably due to ubiquitination and to the proteasome-dependent degradation of the peptide (29,30). PTHrP(1-34) (17 kDa) and other immunoreactive proteins accumulated in H295R cells incubated with a proteasome inhibitor.…”
Section: Pthrp In Adrenocortical Carcinomamentioning
confidence: 99%
“…The amino acid sequence of pro-PTHrP, a precursor of PTHrP, can serve as a substrate for the prohormone convertase furine (29). The PTHrP , detected in H295R cells, but not in adrenal tumors, is probably due to ubiquitination and to the proteasome-dependent degradation of the peptide (29,30). PTHrP(1-34) (17 kDa) and other immunoreactive proteins accumulated in H295R cells incubated with a proteasome inhibitor.…”
Section: Pthrp In Adrenocortical Carcinomamentioning
confidence: 99%
“…Plasmid pcDNA3.1/His-IRP2 was linearized by XbaI and in vitro translated with a TNT-coupled wheat germ kit (Promega) in the presence of [ 35 S]methionine. Assays of ubiquitin conjugation and degradation were performed as previously described (34).…”
Section: Methodsmentioning
confidence: 99%
“…PTHrP is synthesized as a prepro protein that encodes a mature 141-amino acid protein (in the rat) that is post-translationally cleaved to generate the bioactive peptide 1-36 as well as other poorly characterized fragments. While studying the post-translational regulation of PTHrP, we showed that full-length endogenously overexpressed PTHrP was degraded by the ubiquitin-dependent proteolytic system (16). The ubiquitin proteolytic pathway is responsible for the degradation of misfolded or aberrant polypeptides in the cytosol and nucleus (17).…”
mentioning
confidence: 99%